(untitled) (Journal of Hama University, 2022)
The research aims to study the impact of the price policy on irrigated pistachios production in Hama Governorate. To reach this objective, the impact of the pistachios price has been studied on the planted areas and the economic indexes of the crop during (2005-2018). The results show that the annual change rate of pistachios areas is increasing by ca. 178.5 ha at the country level. However, the annual change rate of the pistachios area is growing by 121.9 ha, at the Hama Governorate,the average total costs reach 4,894,280.3 SP/ha and the total revenue reaches 24,457,925 SP/ha. The economic profit is 19,563,644.7 SP/ha, the balance point for production capacity reached (0.17), the farm productive efficiency reaches 22.54. However, the total productive efficiency is 26.87 which indicates to the economic efficiency of pistachios production in the study area, that meaning every one SP invested in the production of this crop returns to the farmer with total return reach (4.99)SP. In addition, the results indicate the occurrence of governmental subsidies to pistachios production. Whereas the higher was logarithm of the price in the last season by one SP/kg the bigger are the planted areas by 381%. The higher logarithm of the global price of pistachios by one SP/kg the more areas planted with irrigated pistachios which means that the government subsidy led to an decrease in the pistachios areas by 32% in Hama.